Determinants of dividend payout: empirical evidence from 44 of the Bursa Malaysia companies / Nur Yasira Yusof - Yusof, Nur Yasira (2017)
This study aims to investigate what are the factors that affecting the dividend payout of a company. 44 largest companies listed under the Bursa Malaysia is chosen as the sample of the study for the time period from 2008 to 2016. This study is also conducted to measure the relationship between these factors with the dividend payout in different industries. From the result, the only significant factors that has impact on dividend payout is firm size, debt ratio and current ratio. While debrato and taxation do not have any significant relationship towards the dividend payout.